2020
DOI: 10.1002/jmv.26398
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of children with coronavirus disease 2019 (COVID‐19)

Abstract: Objective To provide a comprehensive and systematic analysis of demographic characteristics, clinical symptoms, laboratory findings and imaging features of coronavirus disease 2019 (COVID‐19) in pediatric patients. Methods A meta‐analysis was carried out to identify studies on COVID‐19 from December 25, 2019 to April 30, 2020. Results A total of 48 studies with 5829 pediatric patients were included. Children at all ages were at risk for COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
278
8
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(391 citation statements)
references
References 60 publications
35
278
8
10
Order By: Relevance
“…Few studies addressed differences in symptom profiles by age among CYP. A large high-quality review by Cui et al 15 reported that proportions with fever and cough were similar in infants to those in older children, conclusions supported by a small lowquality review by Yasuhara et al 13 In contrast, in a small medium-quality review, Christophers et al 20 reported that fever appeared more common in older children (65%) than in infants (48%). Christophers et al 20 also reported that vomiting and diarrhoea occurred largely in those under 9 years, whereas Yasuhara et al 13 reported gastrointestinal symptoms to be more common in adolescents, although numbers were small and symptoms uncommon in all ages.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Few studies addressed differences in symptom profiles by age among CYP. A large high-quality review by Cui et al 15 reported that proportions with fever and cough were similar in infants to those in older children, conclusions supported by a small lowquality review by Yasuhara et al 13 In contrast, in a small medium-quality review, Christophers et al 20 reported that fever appeared more common in older children (65%) than in infants (48%). Christophers et al 20 also reported that vomiting and diarrhoea occurred largely in those under 9 years, whereas Yasuhara et al 13 reported gastrointestinal symptoms to be more common in adolescents, although numbers were small and symptoms uncommon in all ages.…”
Section: Resultsmentioning
confidence: 98%
“…We included 18 reviews in our analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Characteristics of the included reviews are shown in table 1; all are freely available online (see online supplemental appendix table 2). All reviews were in English.…”
Section: Resultsmentioning
confidence: 99%
“…As a direct consequence, most countries have decided to start their vaccination programs against SARS-CoV-2 with the elderly, alongside the healthcare personnel and high-risk individuals [ 37 ]. Children seem indeed fairly exempt from severe forms of COVID-19 illness [ 38 ], although there have been reports on cardiac abnormalities that should not be underestimated [ 39 ].…”
Section: Spotlight On Original Articlesmentioning
confidence: 99%
“…
A systematic review and meta-analysis of children with coronavirus disease 2019 (COVID-19) [ 1 ] Cui X, et al., J Med Virol 2020 Summary: The authors conducted a systematic review and meta-analysis of articles reporting on pediatric cases of coronavirus disease 2019 (COVID-19) due to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. This article focused on the clinical presentation of COVID-19, including demographic characteristics, disease severity, reported symptoms, laboratory findings and imaging results.
…”
mentioning
confidence: 99%